2021
DOI: 10.1097/fjc.0000000000000995
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ticagrelor in Diabetes Patients Undergoing Percutaneous Coronary Intervention: A Meta-Analysis of Randomized Controlled Trials

Abstract: Dual antiplatelet treatment, consisting of aspirin and P2Y12 inhibitors, is essential for diabetes mellitus (DM) patients who have undergone percutaneous coronary intervention (PCI). This meta-analysis investigated whether ticagrelor, a novel P2Y12 inhibitor, was superior to clopidogrel and prasugrel in efficacy and safety for DM patients undergoing PCI. PubMed, the Cochrane Library and Google Scholar were searched for randomized controlled trials in which ticagrelor was administered. Eligible studies were ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…A recent meta-analysis comparing ticagrelor versus clopidogrel and prasugrel in diabetic patients having undergone PCI showed that ticagrelor-based therapy reduced significantly MACE by 60%. 34 This meta-analysis confirmed previous reports, which claimed that ticagrelor-based DAPT was beneficial, compared with clopidogrel- and prasugrel-based regimens. 35–37 The reasons why ticagrelor monotherapy seems to be associated with less ischemic events compared with ticagrelor-based DAPT remains unknown.…”
Section: Discussionsupporting
confidence: 88%
“…A recent meta-analysis comparing ticagrelor versus clopidogrel and prasugrel in diabetic patients having undergone PCI showed that ticagrelor-based therapy reduced significantly MACE by 60%. 34 This meta-analysis confirmed previous reports, which claimed that ticagrelor-based DAPT was beneficial, compared with clopidogrel- and prasugrel-based regimens. 35–37 The reasons why ticagrelor monotherapy seems to be associated with less ischemic events compared with ticagrelor-based DAPT remains unknown.…”
Section: Discussionsupporting
confidence: 88%